Concordant optimal molecular and cytogenetic responses at both 3 and 6 months predict a higher probability of MR4.5 achievement in patients with chronic myeloid leukemia treated with imatinib. Issue 6 (3rd June 2017) - Qin, Ya-Zhen; Jiang, Qian; Lai, Yue-Yun; Jiang, Hao; Shi, Hong-Xia; Zhao, Xiao-Su; Liu, Yan-Rong; Huang, Xiao-Jun
Abstract: To investigate the impact of the combination of early molecular and cytogenetic responses on the achievement of MR4.5, 228 newly diagnosed chronic phase chronic myeloid leukemia patients treated with imatinib were categorized into 3-month and 6-month concordant optimal, discordant, concordant warning, and failure groups. Among them, 85.3% at 3 months and 78.1% at 6 months had concordant molecularly and cytogenetically defined responses. At both 3 and 6 months, patients with discordant, concordant warning and failure responses had similar 3-year MR4.5 rates, and all were significantly lower than the rate in patients with concordant optimal responses. Patients with concurrent 3-month and 6-month concordant optimal responses had a significantly higher 3-year MR4.5 rate than those with other responses, and 3-month and 6-month concurrent molecular optimal, but not cytogenetic optimal responses. Therefore, achieving concordant optimal molecular and cytogenetic responses at both 3 and 6 months with imatinib treatment are associated with MR4.5 achievement.